New era Dalian Strengthens to People in the Private Economy in Ideological and Political Studies - Li, Kun (Journal of Global Economy, Business and Finance, 2024)
Private economy is an important part of China's national economy, playing an irreplaceable role. In the new era, private economy is faced with various difficulties due to the changes of international economic environment and the development of domestic economic situation. An in-depth analysis of the new characteristics of the ideological and political work of private economic personages in Dalian, by optimizing the development environment of private economy, perfecting the mechanism of ideological and political work of private economy, screening the content of ideological and political work that matches the actual needs of private economy development, and making full use of modern multiple carriers, etc., it is of great significance to strengthen the ideological and political guidance of private economic personages in Dalian.